Boundary Control of Full-Bridge ZVS: Natural Switching Surface for Transient and Steady-State Operation - Oggier, German Gustavo (2014)
This paper presents the use of a high-performance boundary controller for the full-bridge zero-voltage-switching topology. An enhanced dynamic response is obtained by employing the natural switching surface (SS), which is thoroughly derived in the normalized geometrical domain. The advantages of the normalization are the simple graphical representation, the generality for any combination of parameters, and the mathematical simplicity. Recently, nonisolated basic topologies have benefited from advancements in boundary control. The analysis and derivation in this work bring the benefit of outstanding dynamic performance to this isolated topology. As demonstrated in this work, the relationship between the leakage and output filter inductances makes the formulation of the natural trajectories for isolated converters possible. The resulting SS provides an excellent dynamic response during start-up, reference change, and sudden output loading conditions. Experimental results are presented to illustrate the characteristics and advantages of the control scheme and the converter operation with fixed switching frequency.